The Role of Profitability in Moderating the Influence of ESG on Company Value - Nike Dewanti Wulanningrat; Paulus Theodorus Basuki Hadiprajitno (Eduvest - Journal of Universal Studies, 2025)
According to Bloomberg ESG Disclosure (2024), ESG-based investments have reached $35 trillion globally, with Indonesia showing a 45% increase in ESG disclosure among listed companies in 2023. This research analyzes the moderating role of profitability in the relationship between Environmental, Social, and Governance (ESG) performance and firm value in high-risk companies listed on the Indonesia Stock Exchange (IDX) during 2022–2023. Using a quantitative approach and purposive sampling, data were collected from 202 high-risk companies in mining, energy, and chemical sectors. Panel data regression analysis with a fixed effects model was applied, based on Chow and Hausman tests. Findings show that ESG performance alone does not significantly affect firm value. However, when profitability, measured by Return on Assets (ROA), is introduced as a moderator, ESG exhibits a significant negative effect on firm value, while profitability has a significant positive effect. Notably, the interaction between ESG and profitability is significantly negative, indicating profitability weakens, rather than strengthens, ESG’s impact on firm value. This suggests investors perceive ESG efforts in highly profitable, high-risk Indonesian companies as inefficient resource allocation. This research advances signaling theory by showing that ESG implementation is not always viewed positively by investors, particularly in profitable, high-risk firms. The findings have important implications for corporate managers aiming to implement ESG efficiently and for regulators designing policies to encourage ESG adoption in high-risk sectors.